Worlds in Motion: Temporality and Historicality. Issue 3 (26th May 2020) - Staehler, Tanja
ABSTRACT: Worlds are always in motion; what kind of movement is at stake? In this essay, I will argue that Heidegger moves beyond Hegel by making the concept of world central to phenomenology. But how do worlds move? As history, Heidegger says; yet his initial attempt to interpret history, in the final sections of Being and Time, is at certain moments hampered by his attempt to ground the historicality of shared world in the temporality of individual Dasein. Derrida then moves beyond Heidegger by addressing paradoxes in our understanding of time and history. This allows Derrida to introduce the ethical dimension of world from the start as we are called to acknowledge that the Other brings their own world and awaits our response. Worlds are both singular and shared; and in any case, they move (and move us).